X+8-4x+8x=7x+9+5x-2

Simple and best practice solution for X+8-4x+8x=7x+9+5x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+8-4x+8x=7x+9+5x-2 equation:


Simplifying
X + 8 + -4x + 8x = 7x + 9 + 5x + -2

Reorder the terms:
8 + X + -4x + 8x = 7x + 9 + 5x + -2

Combine like terms: -4x + 8x = 4x
8 + X + 4x = 7x + 9 + 5x + -2

Reorder the terms:
8 + X + 4x = 9 + -2 + 7x + 5x

Combine like terms: 9 + -2 = 7
8 + X + 4x = 7 + 7x + 5x

Combine like terms: 7x + 5x = 12x
8 + X + 4x = 7 + 12x

Solving
8 + X + 4x = 7 + 12x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + X + -8 + 4x = 7 + -8 + 12x

Reorder the terms:
8 + -8 + X + 4x = 7 + -8 + 12x

Combine like terms: 8 + -8 = 0
0 + X + 4x = 7 + -8 + 12x
X + 4x = 7 + -8 + 12x

Combine like terms: 7 + -8 = -1
X + 4x = -1 + 12x

Add '-4x' to each side of the equation.
X + 4x + -4x = -1 + 12x + -4x

Combine like terms: 4x + -4x = 0
X + 0 = -1 + 12x + -4x
X = -1 + 12x + -4x

Combine like terms: 12x + -4x = 8x
X = -1 + 8x

Simplifying
X = -1 + 8x

See similar equations:

| 9-(1-3y)=48+y-(3-y) | | 2x-5/-45/4 | | x^2+7*x+29=0 | | (8x+5)-20x=x | | -5(2/3)=(2/3)-6(2/3)= | | -5*2/3= | | 2y-6+3x=0 | | -5(2/3)= | | 7x+5y-3x-8y=1 | | 18y+x=28-3y | | x*x-5=126 | | 2b+3a=1.4 | | X/2=-15=x/5 | | 7y+5=20 | | 4/18=5/x | | 100/x=y | | 22-3(x-2)=2(4+x) | | x+x+x-5y-y-3x= | | 12x+3=-2b-4 | | -4x-4x-7y= | | x^2+3x+4-sqrt(x^2+3x+6)=0 | | 8x^6=2x^2 | | 8x^6=4x^2 | | 3z+6x-5z+2x= | | x^2+3x+4=sqrt(x^2+3x+6) | | 24x+44+55x=55x+64x | | 0.2(b-2)-0.5(b+2)=4.5 | | -16t^2+128t-192=0 | | 6k^2+7k-4-7k^2-11k+4= | | 8-2/p-1=2 | | [4x]-3=-7 | | [6x]-5=7 |

Equations solver categories